EFFICACY OF MOTORIZED INTERMITTENT LUMBAR TRACTION AND WILLIAM FLEXION EXERCISE FOR DECREASING PAIN AND DISABILITY LEVEL IN PATIENTS OF NON-SPECIFIC LOW BACK PAIN - Maria Kokab; Sumaiyah Obaid (Journal of University Medical & Dental College, 2017)
ABSTRACT: OBJECTIVES: Examine effect of Motorized intermittent lumbar traction and find effective treatment for pain and disability in patients of NSLBP. METHODS: 120 patients (mean age 26.51 ± 2.95) with Non-Specific LBP were randomized into two groups. In first group (1) motorized intermittent traction for long period of time with William flexion exercises and in second group (2) only William flexion exercises were given. Hot pack and postural education were given to both groups. Each group included 30 male patients and 30 female patients. Treatment among both groups was conducted for variations in disability level and pain score. RESULTS: Out of 120 subjects, 20 were dropout, 18 from group 1 and 6 from group 2 due to various reasons like financial issue, schedule problems and increase in pain level. Traction group showed greater improvement in pain level (VAS p<0.05). About 73% subjects reported minimal disability in group 1 (p<0.05) and 37% in group 2, which shows that lumbar traction treatment was more effective in reduction of pain and disability score. Conclusion: Owing to the statistical significance difference in current study, and view of sample power due to large number of patients in each group, the results lead to positive conclusion. Therefore, it can be concluded that lumbar traction seems to be more effective than William flexion exercises. In addition, it can be concluded that traction with William flexion exercise is more effective than solo William flexion exercises.